Dihydroartemisinin–piperaquine resistance in Plasmodium falciparum malaria in Cambodia: a multisite prospective cohort study. Issue 3 (March 2016) - Amaratunga, Chanaki; Lim, Pharath; Suon, Seila; Sreng, Sokunthea; Mao, Sivanna; Sopha, Chantha; Sam, Baramey; Dek, Dalin; Try, Vorleak; Amato, Roberto; Blessborn, Daniel; Song, Lijiang; et al.
Summary: Background: Artemisinin resistance in Plasmodium falciparum threatens to reduce the efficacy of artemisinin combination therapies (ACTs), thus compromising global efforts to eliminate malaria. Recent treatment failures with dihydroartemisinin-piperaquine, the current first-line ACT in Cambodia, suggest that piperaquine resistance may be emerging in this country. We explored the relation between artemisinin resistance and dihydroartemisinin–piperaquine failures, and sought to confirm the presence of piperaquine-resistant P falciparum infections in Cambodia. Methods: In this prospective cohort study, we enrolled patients aged 2–65 years with uncomplicated P falciparum malaria in three Cambodian provinces: Pursat, Preah Vihear, and Ratanakiri. Participants were given standard 3-day courses of dihydroartemisinin–piperaquine. Peripheral blood parasite densities were measured until parasites cleared and then weekly to 63 days. The primary outcome was recrudescent P falciparum parasitaemia within 63 days. We measured piperaquine plasma concentrations at baseline, 7 days, and day of recrudescence. We assessed phenotypic and genotypic markers of drug resistance in parasite isolates. The study is registered withClinicalTrials.gov, numberNCT01736319 . Findings: Between Sept 4, 2012, and Dec 31, 2013, we enrolled 241 participants. In Pursat, where artemisinin resistance is entrenched, 37 (46%) of 81 patients had parasite recrudescence. In Preah Vihear, where artemisinin resistance is emerging, ten (16%) of 63 patients had recrudescence and in Ratanakiri, where artemisinin resistance is rare, one (2%) of 60 patients did. Patients with recrudescent P falciparum infections were more likely to have detectable piperaquine plasma concentrations at baseline compared with non-recrudescent patients, but did not differ significantly in age, initial parasite density, or piperaquine plasma concentrations at 7 days. Recrudescent parasites had a higher prevalence of kelch13 mutations, higher piperaquine 50% inhibitory concentration (IC50 ) values, and lower mefloquine IC50 values; none had multiple pfmdr1 copies, a genetic marker of mefloquine resistance. Interpretation: Dihydroartemisinin–piperaquine failures are caused by both artemisinin and piperaquine resistance, and commonly occur in places where dihydroartemisinin–piperaquine has been used in the private sector. In Cambodia, artesunate plus mefloquine may be a viable option to treat dihydroartemisinin–piperaquine failures, and a more effective first-line ACT in areas where dihydroartemisinin–piperaquine failures are common. The use of single low-dose primaquine to eliminate circulating gametocytes is needed in areas where artemisinin and ACT resistance is prevalent. Funding: National Institute of Allergy and Infectious Diseases.